Density and dispersion of reef coral Pocillopora damicornis (Linneaus 1758) in Kalirohan reef flat, Taklong Island Marine Reserve, Guimaras. - Madarcos, Nicci Rosietess E.
Density and dispersion of reef coral Pocilloproa damicornis (Linnaeaus 1758) was investigated in December 2012. Furthermore, the reef flat community structure was compared during wet (October) and dry (December) periods using the line-intercept method to determine live coral cover. The present density P. damicornis in Kalirohan was very low (D=100=- 38 per 1000m squared) and only about tenth of level reported 20 years ago. Dispersion pattern was aggregated. Kalirohan reef flat condition deteriorated quickly from fair (34.51 percent live voral cover) in October to poor (15.73 percent live coral cover) in December likely due to the passage of a strong typhoon in the area. Degradation or deteriorating condition of the reef flat was due to coral death as reflected in the increased coral mortality index (CMI) from 0.37 in october to 0.69 in December.